Early contributors to the success of anti-COVID vaccines - Brian Heap (Elsevier, 2021)
The paper of Gregory Gregoriadis brings into sharp relief the contrast in time taken for 'individual technologies to emerge from research, find market opportunities and make a tangible impact' [1]. This short commentary highlights some early events that were to underpin the success of a new anti-COVID vaccine.